Pengaruh Kepemimpinan Visioner Dan Motivasi Kerja Terhadap Kepuasan Kerja - Sukriadi, Erie Hidayat (Universitas Pendidikan Indonesia, 2018)
The purpose of this research is to analyze the influence of leader’s visionary leadership and work motivation together towards lecturer job satisfaction in the Private Universities Hospitality Study Program in Bandung. The method used in this research is survey method with the level of explanation is associative. The Respondents in this research is using census with total of respondents are 57 respondents. The Data collection techniques are using literature study, study of documentation, and field studies using interviews and questionnaires. The Data analysis technique are using qualitative analysis and statistical analysis. Qualitative analysis includes scores of respondents, while the statistical analysis includes the path analysis. The result of this research shows that the influence of the leader’s visionary leadership and work motivation together towards is at 59,23%.